The economics of the war on illegal drug production and trafficking (2013)
We model the war on drugs in source countries as a conflict over scarce inputs of successive levels of the production and trafficking chain. We explicitly model the vertical structure of the drug trade as being composed of several stages, and study how different policies aimed at different stages affect the supply, prices and input markets. We use the model to study Plan Colombia, a large scale intervention in Colombia aimed at reducing the supply of cocaine by targeting illicit crops and illegal armed groups' control of the routes used to transport drugs outside of the country - two of the main inputs of the production and trafficking chain. The model fits many of the patterns found in the data and sheds light on certain puzzling findings. For a reasonable set of parameters that match well the data on the war on drugs under Plan Colombia, our model predicts that the marginal cost to the U.S. of reducing the amount of cocaine transacted in retail markets by one kilogram is $1'631.900 if resources are allocated to eradication efforts; and $267.450 per kilogram if resources are allocated to interdiction efforts.